Production and marketing of the black clam (Villorita cyprinoides) in Perumbalam Island, Alappuzha District, Kerala - Gopal, Nikita; Jeyanthi, P.; Chandrasekar, V. (Indian Journal of Fisheries, 2014)
The black clam, Villorita cyprinoides is abundant in the Vembanad estuarine system. Perumbalam Island in Alappuzha District is part of the Vembanad estuarine system and black clam fishing has been an important livelihood activity in this region. The resource has been long exploited for its shell, and presently the meat also has a growing domestic market. This paper presents the existing production to marketing chain of black clam in the island. Clam fishing, processing and marketing has been a family centric activity in the region. The operational cost of harvesting and processing clam was ` 24,500/-. The gross and net returns were ` 82,720/- and `58,220/- respectively per family per year. The marketing efficiency was highest for the direct marketing channel i.e., producer to consumer. The harvest of small sized clams had been in vogue earlier, but now the fishers resort to culturing of the clams to bigger sizes before harvesting it. Since the clam fishing activity is having a degree of concentration in the island with a number of households being engaged in it, the possibility of clustering and organising the activity for sustainable harvesting and better processing as well as marketing needs to be explored.